Effects of PARP-1 Deficiency on Th1 and Th2 Cell Differentiation - M. Sambucci; F. Laudisi; F. Novelli; E. Bennici; M. M. Rosado; C. Pioli (The Scientific World Journal)
T cell differentiation to effector Th cells such as Th1 and Th2 requires the integration of multiple synergic and antagonist signals. Poly(ADP-ribosy)lation is a posttranslational modification of proteins catalyzed by Poly(ADP-ribose) polymerases (PARPs). Recently, many reports showed that PARP-1, the prototypical member of the PARP family, plays a role in immune/inflammatory responses. Consistently, its enzymatic inhibition confers protection in several models of immune-mediated diseases, mainly through an inhibitory effect on NF-κB (and NFAT) activation. PARP-1 regulates cell functions in many types of immune cells, including dendritic cells, macrophages, and T and B lymphocytes. Our results show that PARP-1KO cells displayed a reduced ability to differentiate in Th2 cells. Under both nonskewing and Th2-polarizing conditions, naïve CD4 cells from PARP-1KO mice generated a reduced frequency of IL-4+ cells, produced less IL-5, and expressed GATA-3 at lower levels compared with cells from wild type mice. Conversely, PARP-1 deficiency did not substantially affect differentiation to Th1 cells. Indeed, the frequency of IFN-γ+ cells as well as IFN-γ production, in nonskewing and Th1-polarizing conditions, was not affected by PARP-1 gene ablation. These findings demonstrate that PARP-1 plays a relevant role in Th2 cell differentiation and it might be a target to be exploited for the modulation of Th2-dependent immune-mediated diseases.